Evaluation Of Office Relocation of PT. PLN (Persero) Unit Execution Project Nusa Tenggara 2 - Wijaya, Andi; Silaban, Jeffry Frans Rinaldo; Ertyastono, Adrian (Publikasi Indonesia, 2024)
The location of the office of PT PLN (Persero) UPP Kitring Nusra 2 is in Ende Regency approximately 200 kilometers from the project locations currently managed. This makes the process of supervision and coordination with relevant stakeholders difficult. Throughout 2022 until now, work supervision, certification, land, ROW, and licensing activities have dominated the West Flores area. Therefore, for effective and efficient implementation of the main duties and functions, consideration of moving the office location to Labuan Bajo City needs to be done. This study aims to evaluate the feasibility of moving the office. The analysis method was carried out using factor rating and SWOT methods. The results of the comparison of 2 locations using the factor rating method show that the potential office location is in Labuan Bajo with a value of 95.81 and the existing location of Ende City is worth 84.19. Meanwhile, based on SWOT analysis, it was obtained that the location of the office in Labuan Bajo was in quadrant 1, so it can be concluded that the transfer is said to be feasible.